Data Mining Application for Healthcare Sector: Predictive Analysis of Heart Attacks - Fernandes, Maria Inês Resende da Lomba (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence